Visual ground pattern modulates flight speed of male Oriental fruit moth Grapholita molesta. (29th July 2014) - Kuenen, Lodewyk P. S.; Gilbert, Cole
Abstract Insects flying in a horizontal pheromone plume must attend to visual cues to ensure that they make upwind progress. Moreover, it is suggested that flying insects will also modulate their flight speed to maintain a constant retinal angular velocity of terrestrial contrast elements. Evidence from flies and honeybees supports such a hypothesis, although tests with male moths and beetles flying in pheromone plumes are not conclusive. These insects typically fly faster at higher elevations above a high‐contrast ground pattern, as predicted by the hypothesis, although the increase in speed is not sufficient to demonstrate quantitatively that they maintain constant visual angular velocity of the ground pattern. To test this hypothesis more rigorously, the flight speed of male oriental fruit moths (OFM) Grapholita molesta Busck (Lepidoptera: Tortricidae) flying in a sex pheromone plume in a laboratory wind tunnel is measured at various heights (5–40 cm) above patterns of different spatial wavelength (1.8–90°) in the direction of flight. The OFM modulate their flight speed three‐fold over different patterns. They fly fastest when there is no pattern in the tunnel or the contrast elements are too narrow to resolve. When the spatial wavelength of the pattern is sufficiently wide to resolve, moths fly at a speed that tends to maintain a visual contrast frequency of 3.5 ± 3.2 Hz rather than a constant angular velocity, which varies from 57 to 611° s−1. In addition, for the first time, it is also demonstrated that the width of a contrast pattern perpendicular to the flight direction modulates flight speed.